2002
DOI: 10.1007/s198-002-8334-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Collagen and Mineral Content on the High-Frequency Ultrasonic Properties of Human Cancellous Bone

Abstract: The technology surrounding ultrasonic bone assessment is evolving rapidly as investigators explore the utility of new ultrasonic parameters and different ultrasonic frequencies. This study had three main goals. The first was to perform in vitro measurements of the speed of sound (SOS) and normalized broadband ultrasonic attenuation (nBUA) in specimens of normal human cancellous bone using a 2.25 MHz broadband measurement system. The second was to explore the utility of a backscatter-based parameter called appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 20 publications
(36 reference statements)
2
41
1
Order By: Relevance
“…A similar relationship between backscattering and BMD was found by Nicholson and Bouxsein (2002) in vitro and by Wear and Garra (1998) in vivo. In contrast to those studies, Hoffmeister et al (2000Hoffmeister et al ( , 2002 found no systematic linear relationship between backscattering and BMD. This discrepancy may be attributed to the varying frequency range used in the determination of backscattering, differences between in vitro and in vivo measurement environments and/or differences between human calcaneus and bovine trabecular bone.…”
Section: Introductioncontrasting
confidence: 76%
See 4 more Smart Citations
“…A similar relationship between backscattering and BMD was found by Nicholson and Bouxsein (2002) in vitro and by Wear and Garra (1998) in vivo. In contrast to those studies, Hoffmeister et al (2000Hoffmeister et al ( , 2002 found no systematic linear relationship between backscattering and BMD. This discrepancy may be attributed to the varying frequency range used in the determination of backscattering, differences between in vitro and in vivo measurement environments and/or differences between human calcaneus and bovine trabecular bone.…”
Section: Introductioncontrasting
confidence: 76%
“…Most QUS examinations are performed in the calcaneus, which is not a typical site of fracture. As suggested by Chaffai et al (2002) and others (Hoffmeister et al 2002;Roux et al 2001), the direct measurement of QUS parameters at fracture sites such as the hip and wrist would probably improve the diagnostic capability of US.…”
Section: Discussion and Summarymentioning
confidence: 93%
See 3 more Smart Citations